Analyse quantitative du réseau hydrographique du bassin versant du Slănic (Roumanie) - Florina Grecu; Ion Zăvoianu; Liliana Zaharia; Laura Comănescu (Physio-Géo)
The study is focused on the Slănic basin which has a small size (433 km2). The hydrographical basin of Slănic, situated in the Carpathian and Subcarpathian Curvature, a very active from neotectonical viewpoint area, is a part of the Buzău basin. From a petrographic point of view, the Slănic hydrographic basin belongs to the paleogen flysch deposits (within the Carpathian sector) and to the mio-pliocen molasse (within the Subcarpathian area) latter formed by predominantely friable rocks which have encouraged deep fragmentation of the relief. Actual rainfalls are often very intensive, and they frequently occur after dry seasons. The analysis of morphometric parameters shows many elementary segments of first order (5230 river segments) and second order (944 river segments), a high density of drainage (15 river segments / km2), and the medium length for first order (260 m) and second order (530 m) segments.The big number of the river segments of inferior orders presupposes a speed response of the basin to the torrential rains and flows of high energy. The speed response of the inferior segments is further encouraged by the spatial distribution of rainfall and lithologic conditions.